Penerapan Metode Inquiry untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV-A di MI Mazra’atul Ulum 02 Paciran - Hasan, Muhammad Nur; Izza, Adibatul; Mukti, Taufiq Satria (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to improve the learning outcomes of Natural and Social Sciences (IPAS) of class IV A students at MI Mazra'atul Ulum 02 Paciran through the application of the inquiry method. The inquiry method was chosen because it is believed to be able to foster curiosity, develop critical thinking skills, and improve students' understanding of concepts actively. This study uses a classroom action research (PTK) method which is carried out in two cycles. Each cycle includes planning, action, observation, and reflection. The subjects of the study were 18 students of class IV A MI Mazra'atul Ulum 02 Paciran in the 2024/2025 academic year. Data on students' IPAS learning outcomes were collected through formative tests at the end of each cycle. The results of the study showed an increase in students' IPAS learning outcomes after the application of the inquiry method. The percentage of student learning completion increased in cycle I by 50% and in cycle II by 77.7%. In addition, observations showed an increase in student activity and involvement in the learning process. Thus, it can be concluded that the application of the inquiry method is effective in improving the science learning outcomes of class IV A students at MI Mazra'atul Ulum 02 Paciran.